Díez Gutiérrez, E. J. (2018). Neoliberalismo educativo. Barcelona: Octaedro - Monarca, Héctor (Journal of Supranational Policies of Education (JOSPOE), 2019)
Díez Gutiérrez, E. J. (2018). Neoliberalismo educativo. Barcelona: Octaedro